2004
DOI: 10.7883/yoken.jjid.2004.236
|View full text |Cite
|
Sign up to set email alerts
|

Defense Mechanisms against Influenza Virus Infection in the Respiratory Tract Mucosa

Shin-ichi Tamura,
Takeshi Kurata

Abstract: The respiratory tract mucosa is not only the site of infection for influenza viruses but also the site of defense against virus infection. Viruses are initially detected and destroyed non-specifically by innate immune mechanisms, but if the viruses escape the early defense mechanisms, they are detected and eliminated specifically by adaptive immune mechanisms. The major adaptive immune mechanisms are as follows. (i) Specific secretory-IgA (S-IgA) antibodies (Abs) and CTLs (CD8 + cytotoxic T lymphocytes) are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…Mucosal vaccination is widely regarded as the most effective approach for combating infectious diseases caused by pathogens. Recent advancements in mucosal vaccines have demonstrated their ability to provide superior protection against both systemic and mucosal infections, which are the primary entry points for most pathogenic microorganisms [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Mucosal vaccination is widely regarded as the most effective approach for combating infectious diseases caused by pathogens. Recent advancements in mucosal vaccines have demonstrated their ability to provide superior protection against both systemic and mucosal infections, which are the primary entry points for most pathogenic microorganisms [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Influenza infection causes considerable morbidity and mortality and affects people at all ages, hence posing a threat to human health globally [2,3]. Influenza A virus (IAV) infection elicits host innate and adaptive immune responses that are the key host antiviral defense mechanisms to restrain virus replication and spread [4][5][6]. It has been demonstrated that pulmonary CD8 + cytotoxic T lymphocytes (CTLs) play a central role in the clearance of IAV due to their ability to specifically recognize and directly destroy the IAV-infected cells [6][7][8].…”
Section: Introductionmentioning
confidence: 99%